Field relations, structure, and geochemistry of the Fisset Brook Formation in the Lake Ainslie - Gillanders Mountain area, central Cape Breton Island, Nova Scotia - Barr, S.; Macdonald, A.; Arnott, A.; Dunning, G. (Atlantic Geology, 1995)
Detailed mapping shows that the Fisset Brook Formation in the Lake Ainslie - Gillanders Mountain area consists of a lowermost sedimentary unit overlain by basaltic and rhyolitic units. The sedimentary unit is mainly arkosic pebble conglomerate and siltstone, and unconformably overlies or is in faulted contact with older meta-morphic and plutonic rocks. Scattered gabbroic plutons and dykes in the sedimentary unit are interpreted to represent "feeders" to the overlying basaltic flows. The basaltic unit consists mainly of subaerial flows, locally interlayered and intermixed with red-brown siltstone. The overlying rhyolitic unit consists mainly of eutaxitic to spherulitic flows or welded tuffs, with less abundant lapilli tuff. In the Lake Ainslie area, these rocks occur in a north-south array of rhombic fault blocks, whereas in the Gillanders Mountain area, the dominant structure is a large-scale anticlinal fold closing toward the south, cored largely by rocks of the Fisset Brook Formation. The chemical compositions of the basalt and rhyolite in both areas have been modified by alteration, but discrimination diagrams using relatively immobile elements, including rare-earth elements, indicate that the basalts and gabbros are continental, within-plate tholeiites. The rhyolites also have features indicative of origin in a within-plate setting, but are depleted in Y, Zr, and rare-earth elements compared to A-type granites. A rhyolite sample yielded a U-Pb (zircon) age of 373 ± 4 Ma, thus indicating that the Fisset Brook Formation in the Lake Ainslie - Gillanders Mountain area is Middle to earliest Late Devonian in age, not Late Devonian to Early Carboniferous as previously inferred.